Repatriation reader : who owns American Indian remains? - Mihesuah, Devon A., 1957- (University of Nebraska Press, 2000)
In the past decade the repatriation of Native American skeletal remains and funerary objects has become a lightning rod for radically opposing views about cultural patrimony and the relationship between Native communities and archaeologists. In this unprecedented volume, Native Americans and non-Native Americans within and beyond the academic community offer their views on repatriation and the ethical, political, legal, cultural, scholarly, and economic dimensions of this hotly debated issue. While historians and archaeologists debate continuing non-Native interests and obligations, Native American scholars speak to the key cultural issues embedded in their ancestral pasts. A variety of sometimes explosive case studies are considered, ranging from Kennewick Man to the repatriation of Zuni Ahayu:da. Also featured is a detailed discussion of the background, meaning, and applicability of the Native American Graves Protection and Repatriation Act, as well as the text of the act itself.